Effect of Viral Marketing to Image B2B Exhibition - Gilang Pratama (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2017)
Problems that facing business to business exhibition in present-day is the lack of communication in using digital marketing, company cannot build image of exhibition and bring more visitor. This study uses viral marketing that measured with audience reach, diffusion of speed and peer to peer transmission as independent variables that can affect towards image of exhibitions as the dependent variable. This study is proving that is important for companies to be able to use the new tool in promotional mix especially the internet to advertise their products and services using social media. Hypothesis analyzed using SEM and by the statistical methods of non-hierarchical (K-means Cluster). The analysis generating result that hypothesis is accepted, and proved that viral marketing with variable Audience of reach, Diffusion of Speed and Peer-to-Peer Transmission affecting towards Image of exhibition Franchise License Expo. This study will further enrich the study of digital marketing especially viral marketing. Abstrak: Masalah yang dihadapi industri pameran dengan jenis business to business di masa kini adalah kurangnya komunikasi dalam menggunakan pemasaran digital, perusahaan tidak bisa membangun citra pameran dan membawa lebih banyak visitor secara efektif dan efisien. Penelitian menggunakan viral marketing yang diukur dengan audience reach, diffusion of speed dan peer to peer transmission sebagai variabel independen yang dapat mempengaruhi terhadap citra pameran sebagai variabel dependen. Penelitian ini membuktikan bahwa penting bagi perusahaan untuk dapat menggunakan alat baru dalam bauran promosi terutama internet untuk mengiklankan produk dan layanan mereka menggunakan media sosial. Hipotesis dianalisis menggunakan SEM dan dengan metode statistik non-hirarkis (K-means Cluster). Hasil analisis menghasilkan hipotesis yang diterima, dan membuktikan bahwa viral marketing dengan variabel audience of reach, diffusion of speed and peer-to-peer transmission mempengaruhi terhadap Image Pameran. Penelitian ini lebih lanjut akan memperkaya studi tentang pemasaran digital terutama viral marketing. Keywords: Viral, Digital Marketing, Promotional Mix, Image, Exhibition. JEL Classification: M30